Lashing In Qanun Aceh And The Convention Against Torture: A Critical Appraisal - Muhammadin, F.; Wicaksono, D.; Sari, A.; Ayutama, O. (Universiti Sains Islam Malaysia, 2024)
While considered archaic to some, the Islamic Sharia applies lashing as punishment for a number of penal offences. Aceh is a special province in Indonesia with the privilege to apply some level of Islamic Sharia. Among them is to apply lashing as punishment for crimes such as fornication, gambling, consuming alcoholic beverages, and many others. Some have criticized this punishment as a violation of the prohibition against torture and cruel treatment. Based on a mix of normative and empirical research, his article will explore the relevant sources of international law and examine whether or not such a claim is true. It will be found that the Islamic Sharia version of lashing as applied in Aceh does not violate this prohibition, except in a very narrow-minded view of international law which may be an intellectual legacy of colonialism towards the world.